HAK MINORITAS: KEWAJIBAN DAN EKUITAS - Budi, Aisyah (Jurnal Akuntansi dan Keuangan Indonesia, 2004)
This article contains a brief discussion about the position of the minority’s interest in the balance sheet. There have been arguments about where to put minority interest in the balance sheet. There are three alternatives: in the liabilities, stockholders’ equity, or between liabilities and stockholders’ equity. These alternatives are based on two consolidation theories, parent company theory and entity theory. This article is expected to give a broader perspective and more knowledge about minority interest, a simple account on balance sheet that is less attractive. At the end of the article, the writer gives her own opinion and conclusion about the nature of the minority interest and the position in the balance sheet.